ANALISIS HUBUNGAN GEOMETRIK JALAN TERHADAP KESELAMATAN JALAN BYPASS MOJOKERTO KM SBY 51-63 - Al’Adilah; Akhmad Hasanuddin; Willy Kriswardhana (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2021)
Bypass Mojokerto is main route of transportation between cities and provinces used to divert areas with high density activities. Based on data from Satlantas Mojokerto, traffic accidents throughout 2019 contained 436 accident cases with 57 people died. The causative factor for traffic accidents is geometric conditions of road that unsuitable with standard design Bina Marga in 1997. Therefore needed to analyze the geometric relationship between roads and road safety on section of Bypass Mojokerto KM Sby 51 – KM Sby 63. The research data used road geometric including radius of the curve, degree of curvature, and superelevation as well as the safety element data including value of the Equivalent Accident Number (EAN), accident number, and accident rate. Field survey was conducted to determine location of bend in KM. Then data processing uses googlemaps and google earth. Meanwhile, safety element data was obtained from Mojokerto Police. Geometric road data obtained were processed using Autocad and calculations were using excel. In this researh, the analysis used to analyze effect of relationship is the statistical test method of linear, multiple, and polynomial regression analysis using excel. The results of three analyzes were compared in order to obtain the percentage value that had the greatest influence on traffic safety. Based on research results, road geometric can have the best affect on road safety are superelevation, degree of curvature and slope with R2 each values of 39.34%; 49.94%; 35.65%. The results of superelevation analysis of road safety using polynomial regression analysis with a value of R2 = 0.393 and Y = -46518X2 + 4716.3X - 100.92. Meanwhile, the results of degree of curvature on road safety using polynomial regression analysis has a value of R2 = 0.499 and Y = 0.0002X2 - 0.0123X + 0.2412. In addition, the results of road safety slope analysis used polynomial regression analysis has a value of R2 = 0.356 and Y = 6.1457X2 - 9.3246X + 6.4163.